Snake bite management in a toddler: a case report in Sumbawa Besar - Ferry Liwang; Fitria Nuraeni; Mulya R. Karyanti (Paediatrica Indonesiana, 2021)
Snake bite is an often-neglected,1 life-threatening emergency prevalent in rural areas of tropical countries such as Indonesia.2 The WHO reported a worldwide incidence of 5 million snake bites per year, with 100,000–200,000 deaths.3 The incidence rate and likelihood of subsequent complications are higher in children than adults.4 According to the WHO, 35% of child deaths related to poisonous animal bites are attributable to snake bites and occur more frequently in boys than girls.5 In Indonesia, no national epidemiological data on snake bites in children is available, but the WHO estimated that 5–8 snake bite cases occur weekly in Lombok, West Nusa Tenggara.6 Lower limbs are the most common site for bites (72%), while facial bites are quite rare (10%).7 Bites involving children and/or the face are considered as severe envenomation and usually require antivenom at an appropriate dose and timing to be effective.8 Therefore, it is important that hospitals are equipped with life-saving intervention measures to optimize care and improve the chances of survival.9 Nevertheless, in developing countries, the use of antivenom is limited by the absence of standardized guidelines, scarcity/unavailability, and high cost.9 In Indonesia, the only antivenom, serum antibisa ular (SABU), is costly and difficult to obtain due to limited quantities, especially in rural areas. Furthermore, SABU is a polyvalent antivenom with low coverage, as it is only indicated for Naja sputatrix, Bungarus fasciatus, and Agkistrodon rhodostoma, despite the numerous other snake species endemic to Indonesia.2